2022
DOI: 10.3389/fphar.2022.806010
|View full text |Cite
|
Sign up to set email alerts
|

Green and Roasted Coffee Extracts Inhibit Interferon-β Release in LPS-Stimulated Human Macrophages

Abstract: The anti-inflammatory activity of coffee extracts is widely recognized and supported by experimental evidence, in both in vitro and in vivo settings, mainly murine models. Here, we investigated the immunomodulatory properties of coffee extracts from green (GCE) and medium-roasted (RCE) Coffea canephora beans in human macrophages. The biological effect of GCE and RCE was characterized in LPS-stimulated THP-1-derived human macrophages (TDM) as a model of inflammation. Results showed decreased amounts of TNF-α, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…THP-1 X-Blue™ monocytes were seeded in 100 mm cell culture dishes (Corning, Borre, France), 5 × 10 6 cells per dish in 10 mL of medium, and differentiated to TDM by exposure to 100 ng/mL of phorbol 12-myristate 13-acetate (PMA, InvivoGen, San Diego, CA, USA) for 3 days, as previously described [ 57 , 58 ]. Monocyte-to-macrophage differentiation was assessed by optical microscopy inspection.…”
Section: Methodsmentioning
confidence: 99%
“…THP-1 X-Blue™ monocytes were seeded in 100 mm cell culture dishes (Corning, Borre, France), 5 × 10 6 cells per dish in 10 mL of medium, and differentiated to TDM by exposure to 100 ng/mL of phorbol 12-myristate 13-acetate (PMA, InvivoGen, San Diego, CA, USA) for 3 days, as previously described [ 57 , 58 ]. Monocyte-to-macrophage differentiation was assessed by optical microscopy inspection.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that after the combination of LPS and TLR 4, IRF 3 can be activated via phosphorylation of kinases TANK-binding kinase 1 (TBK1) and inhibitor of NF-κB (IκB) kinase (IKKε), inducing ISG to produce IFN-Is, modulating the process of inflammation [ 103 ]. In a separate study, Artusa et al reported that green coffee and roasted coffee extract can inhibit the effect of IRF 3, thereby inhibiting excessive IFN-β-induced inflammation [ 104 ]. Conversely, during viral infection, gastrodin (GTD) can promote the activation of IRF 3 in macrophages to facilitate the production of IFN-Is, resisting inflammation and anti-viral infection [ 105 ].…”
Section: Type I Interferon Signaling In Inflammationmentioning
confidence: 99%
“…The health-promoting potential of plant extracts and plant-derived secondary metabolites is widely recognised [186][187][188]. Numerous beneficial effects of polyphenols on human health, such as antioxidant [189][190][191][192][193], anti-inflammatory [194][195][196], immunomodulatory [197][198][199], cardioprotective [200][201][202], neuroprotective [203][204][205], anti-carcinogenic [206][207][208], and prebiotic properties [209], have been reported. Thanks to the plethora of chemical structures they exhibit, natural anticancer compounds may act as cytotoxic agents [210][211][212], anti-mitotic agents [213], angiogenesis inhibitors [214,215], topoisomerase inhibitors [216], apoptosis inducers [217] and cancer invasion [218], migration [219] and proliferation inhibitors [220][221][222].…”
Section: Ellagic Acid and Urolithinsmentioning
confidence: 99%